Growth hormone receptor abundance in tibial growth plates of uremic rats: GH/IGF-I treatment - Edmondson, Stephanie R.; Baker, Naomi L.; Oh, Jun; Kovacs, Gabor; Werther, George A.; Mehls, Otto (Kidney international, 2015)
Growth hormone receptor abundance in tibial growth plates of uremic rats: GH/IGF-I treatment. - Background - Children with chronic renal failure (CRF) exhibit growth retardation and a disturbed growth hormone/insulin-like growth factor-I (GH/IGF-I) axis. Treatment of children with CRF with GH or GH/IGF-I can partially restore linear growth. The molecular basis for decreased longitudinal growth is not known but may involve an impaired action of GH. - Methods - We used the growth-retarded uremic rat model to determine the abundance and distribution of GH receptors (GHRs) in the tibial epiphyseal growth plate and the influence of GH, IGF-I, or combined GH/IGF-I treatment. Pair-fed rats were used as the control. - Results - While all treatment regimes increased body length and weight in both rat groups, only GH/IGF-I treatment increased the total growth plate width. This involved an increase in cell number in the hypertrophic zone, which could also be induced by IGF-I alone. Immunohistochemical analysis showed that uremic rats had decreased abundance of GHRs in the proliferative zone, and only GH/IGF-I therapy could overcome this decrease. These data thus suggest that growth retardation in uremic rats is, at least in part, due to a decrease in GHR abundance in chondrocytes of the proliferative zone of the tibial growth plate. This decreased GHR abundance can be overcome by combined GH/IGF-I therapy, thus enhancing generation and proliferation of hypertrophic zone chondrocytes and increasing growth-plate width. - Conclusion - These studies point to a mechanism for the growth retardation seen in children with CRF, and suggest that combined GH/IGF-I treatment may provide more effective therapy for these patients than GH alone.
Available online 16 December 2015
Gesehen am 12.01.2021